Solve using the elimination method. -2x + 9y = 56 9x – 9y = 0?

2 Answers

Jon Asaviour Profile
Jon Asaviour answered
-2x + 9y = 56 -
9x - 9y = 0
------
7x = 56
x = 56 / 7
x = 8
-2x + 9y = 56 ------ (1)
applying the value of x in equation (1)
-2(8) + 9y = 56
-16 + 9y = 56
9y = 56 + 16
y = 72/9
y = 8

x = 8  ; y = 8
Oddman Profile
Oddman answered
Add the two equations
  (-2x + 9y) + (9x - 9y) = (56) + (0)
  7x = 56
  x = 8
The second equation tells us y = x, so the solution is
  (x, y) = (8, 8)

Answer Question

Anonymous